Green infrastructure for stormwater control as a measure of adaptation to climate change - Borge-Leandro, David (2024)
The present work arose from the need for an exhaustive bibliographic review on green infrastructure for runoff control, since in the field of green and sustainable construction, it is very necessary to have validated information on the benefits of this type of solutions based on nature. For the scientific community, it is very valuable to know the new trends, the different typologies and the solutions that can be implemented in the American tropics or the lack of scientific information as a starting point for new research and development processes. As a methodological approach, Scopus and Web of Science databases were analyzed, using 1138 scientific publications, of all of them, not a single publication was recorded in a language other than English or Mandarin Chinese, using the Bibliometrix package in R. The main ones the results obtained in this work were the following: efficiency in the combination of different typologies, lack of research registered in the databases consulted for Latin America, existence of authors of Latin American origin although their research is in other latitudes. As a general conclusion, more research is required from the Latin American region in English within the most important databases.